2013
DOI: 10.1136/bjsports-2013-092458
|View full text |Cite
|
Sign up to set email alerts
|

Practical responses to confidentiality dilemmas in elite sport medicine

Abstract: Citation: MALCOLM, D. and SCOTT, A., 2014. Practical responses to confidentiality dilemmas in elite sport medicine. British Journal of Sports Medicine, 48 (19), pp. 1410Medicine, 48 (19), pp. -1413 Additional Information:• Results: Clinicians identified three contextual factors which influenced issues related to patient confidentiality in sports medicine: the use of confidentiality waivers; the facilities available for treatment; and the cultural norms of elite sport. They further identified interpersona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Thirdly, Malcolm and Scott's research conducted with members of the British Olympic Association's Medical Committee and Physiotherapy Forum found much more consistent recognition of the privileged nature of patient information [24]. These interviewees again reported that athletes' contracts frequently required them to waive medical confidentiality but noted that, when athletes resisted these obligations, clinicians were required to develop interpersonal strategies to minimize conflicts of interest.…”
Section: Operationalizing Patient Confidentiality In Sportmentioning
confidence: 93%
See 4 more Smart Citations
“…Thirdly, Malcolm and Scott's research conducted with members of the British Olympic Association's Medical Committee and Physiotherapy Forum found much more consistent recognition of the privileged nature of patient information [24]. These interviewees again reported that athletes' contracts frequently required them to waive medical confidentiality but noted that, when athletes resisted these obligations, clinicians were required to develop interpersonal strategies to minimize conflicts of interest.…”
Section: Operationalizing Patient Confidentiality In Sportmentioning
confidence: 93%
“…This environment may therefore expose the clinician to well-meaning questions from concerned teammates [23] and stimulates management demands for prognoses. The openness of sports medicine treatment is compounded by the design of treatment facilities in sport which conventionally have little regard for athlete-patients' privacy [7,24].…”
Section: Contextual Factors Influencing Confidentiality In Sports Medmentioning
confidence: 99%
See 3 more Smart Citations